Clinical and molecular associations with outcomes at 2 years after acute knee injury: a longitudinal study in the Knee Injury Cohort at the Kennedy (KICK). (September 2021) - Garriga, Cesar; Goff, Megan; Paterson, Erin; Hrusecka, Renata; Hamid, Benjamin; Alderson, Jennifer; Leyland, Kirsten; Honeyfield, Lesley; Greenshields, Liam; Satchithananda, Keshthra; Lim, Adrian; Arden, Nigel K; et al.
Summary: Background: Joint injury is a major risk factor for osteoarthritis and provides an opportunity to prospectively examine early processes associated with osteoarthritis. We investigated whether predefined baseline demographic and clinical factors, and protein analytes in knee synovial fluid and in plasma or serum, were associated with clinically relevant outcomes at 2 years after knee injury. Methods: This longitudinal cohort study recruited individuals aged 16–50 years between Nov 1, 2010, and Nov 28, 2014, across six hospitals and clinics in London, UK. Participants were recruited within 8 weeks of having a clinically significant acute knee injury (effusion and structural injury on MRI), which was typically treated surgically. We measured several predefined clinical variables at baseline (eg, time from injury to sampling, extent and type of joint injury, synovial fluid blood staining, presence of effusion, self-reported sex, age, and BMI), and measured 12 synovial fluid and four plasma or serum biomarkers by immunoassay at baseline and 3 months. The primary outcome was Knee Injury and Osteoarthritis Outcome Score (KOOS4 ) at 2 years, adjusted for baseline score, assessed in all patients. Linear and logistic regression models adjusting for predefined covariates were used to assess associations between baseline variables and 2-year KOOS4 . This study is registered with ClinicalTrials.gov, number NCT02667756 . Findings: We enrolled 150 patients at a median of 17 days (range 1–59, IQR 9–26) after knee injury. 123 (82%) were male, with a median age of 25 years (range 16–50, IQR 21–30). 98 (65%) of 150 participants completed a KOOS4 at 2 (or 3) years after enrolment (50 participants were lost to follow-up and two were withdrawn due to adverse events unrelated to study participation); 77 (51%) participants had all necessary variables available and were included in the core variable adjusted analysis. In the 2-year dataset mean KOOS4 improved from 38 (SD 18) at baseline to 79 (18) at 2 years. Baseline KOOS4, medium-to-large knee effusion, and moderate-to-severe synovial blood staining and their interaction significantly predicted 2-year KOOS4 (n=77; coefficient −20·5, 95% CI −34·8 to −6·18; p=0·0060). The only predefined biomarkers that showed independent associations with 2-year KOOS4 were synovial fluid MCP-1 (n=77; −0·015, 0·027 to −0·004 per change in 1 pg/mL units; p=0·011) and IL-6 (n=77; −0·0005, −0·0009 to −0·0001 per change in 1 pg/mL units; p=0·017). These biomarkers, combined with the interaction of effusion and blood staining, accounted for 39% of outcome variability. Two adverse events occurred that were linked to study participation, both at the time of blood sampling (one presyncopal episode, one tenderness and pain at the site of venepuncture). Interpretation: The combination of effusion and haemarthrosis was significantly associated with symptomatic outcomes after acute knee injury. The synovial fluid molecular protein response to acute knee injury (best represented by MCP-1 and IL-6) was independently associated with symptomatic outcomes but not with structural outcomes, with the biomarkers overall playing a minor role relative to clinical predictors. The relationship between symptoms and structure after acute knee injury and their apparent dissociation early in this process need to be better understood to make clinical progress. Funding: Versus Arthritis, Kennedy Trust for Rheumatology Research, and NIHR Oxford Biomedical Research Centre.